Translational vascular medicine pathogenesis, diagnosis, and treatment - Handler, Clive; Dashwood, Michael; Coghlan, Gerry (Springer, 2012)
Modern medicine is increasingly focused on integrating the results of basic scientific research and clinical research, "translational medicine" to provide improved patient care. This collaborative approach which is a "two way street" has proven very useful in various fields in cardiovascular medicine.     Translational Vascular Medicine: Pathogenesis, Diagnosis, and Treatment provides extensive information on new and exciting advances in such topics as surgery and non-pharmacological treatments for atherosclerotic disease of the aorta, pulmonary arterial hypertension, cytoprotective mechanisms in the vasculature, and the "Broken Heart Syndrome". The Editors and their expert panel of contributors have explored the bi-directional and integrated approaches of translational cardiovascular medicine, linking basic science to patient care.   This book is a highly useful method to understand these complex topics and provides considerable insight into important areas of translational cardiovascular medicine and key bibliographies for the reader.